Engaging social activities prevent stroke and myocardial infraction by raising awareness of warning symptoms: A cross-sectional survey study - Kim, Gahyeon; Jang, Hyeokjoo; Kwon, Sebin; Lee, Bumyeol; Jang, Suk-Yong; Chae, Wonjeong; Jang, Sung-In (Frontiers in Public Health, 2023)
Background: Stroke and myocardial infarction (MI) are medical emergencies, and early treatment within the golden hour is crucial for good prognosis. Adequate knowledge about the warning symptoms can shorten the onset-to-door time. Various factors affect the level of awareness, including social activity. This study aimed to determine if engaging in social activity is associated with the awareness of the warning symptoms of stroke and MI. Methods: This cross-sectional study analyzed 451,793 participants from the 2017 and 2019 Korea Community Health Survey. Based on five questions for each of stroke and MI symptoms, participants were divided into an awareness group (replied ‘Yes’ to all five questions) and unawareness group. Engagement in social activities (i.e. religious, friendship, leisure, and volunteer activity) was evaluated through a questionnaire. Multiple logistic regression analysis was performed to evaluate the relation between social activity and awareness of warning symptoms. Results: Overall, 52.6% participants were aware of the warning symptoms of stroke, and 45.8% of MI. Regular engagement in at least one social activity, particularly friendship or volunteer activity, was associated with better awareness of the warning symptoms, both stroke (OR: 1.21, 95% CI: 1.20-1.23) and MI (OR: 1.22, 95% CI: 1.20-1.24). Additionally, more diverse types of social activities were associated with higher levels of awareness. Relationship between social activity and awareness showed positive association with participants older than 60 years, rural residents, or with low socioeconomic status. Conclusion: Engagement in social activity was significantly associated with better knowledge about the warning symptoms of stroke and MI. For early hospital treatment after symptom onset, participation in social activities could be beneficial.